2016
DOI: 10.1007/s00247-016-3599-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of gadobutrol in more than 1,000 pediatric patients: subanalysis of the GARDIAN study, a global multicenter prospective non-interventional study

Abstract: BackgroundGadobutrol is a gadolinium-based contrast agent, uniquely formulated at 1.0 mmol/ml. Although there is extensive safety evidence on the use of gadobutrol in adults, few studies have addressed the safety and tolerability of gadobutrol in pediatric patients.ObjectiveThis subanalysis of data from the GARDIAN study evaluated the safety and use of gadobutrol in pediatric patients (age <18 years).Materials and methodsThe GARDIAN study was a large phase IV non-interventional prospective multicenter post-aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
(26 reference statements)
3
14
0
6
Order By: Relevance
“…These compounds have been used for over 25 years with an excellent safety profile other than the association with nephrogenic systemic fibrosis in those with renal impairment (2,3). Several investigations (4)(5)(6)(7) into the use of these compounds in children have shown that they are safe for use in MR examinations, and have fewer adverse outcomes in children than in adults.…”
mentioning
confidence: 99%
“…These compounds have been used for over 25 years with an excellent safety profile other than the association with nephrogenic systemic fibrosis in those with renal impairment (2,3). Several investigations (4)(5)(6)(7) into the use of these compounds in children have shown that they are safe for use in MR examinations, and have fewer adverse outcomes in children than in adults.…”
mentioning
confidence: 99%
“…There was no difference in diagnostic efficacy results among paediatric age groups or between paediatric and adult patients [ 12 ]. These data are supported by a subgroup analysis of 1142 children (aged < 18 years) [ 17 ] enrolled in the prospective, noninterventional, multinational GARDIAN study ( n > 23,000) [ 18 ], with investigators rating gadobutrol-enhanced MRI as good or excellent in 98% of paediatric patients [ 17 ]. Further support for its diagnostic efficacy in very young paediatric patients comes from a single-centre, observational study in 60 infants aged 4 days to 22.7 months (mean age 11.1 months) who underwent gadobutrol-enhanced MRI of various body regions or MRA [ 19 ].…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 89%
“…As a contrast agent for MRI and MRA, intravenous gadobutrol has a very good and well established safety profile based on extensive evidence (> 50 million doses as of April 2018 [ 50 ]) from the clinical trial and real-world settings [ 8 , 17 , 18 , 51 56 ], with most adverse drug reactions (ADRs) of mild to moderate intensity and transient in nature [ 8 , 11 , 12 , 18 ]. The most common ADRs (incidence 1–10%) were headache and nausea [ 12 ].…”
Section: Tolerability and Safety Of Gadobutrolmentioning
confidence: 99%
“…The safety of gadobutrol was investigated intensively in the “most vulnerable age groups,” ie, children (including neonates) and patients ≥65 years of age. While Hahn et al 23 looked at children aged 2 to 17 years in a clinical phase 2 setting, Glutig et al 24 took the more real-life perspective of an observational trial, including children aged younger than 2 years as well. A specific study on PK and safety of gadobutrol in children aged younger than 2 years including term newborns was performed by Kunze et al 25 They investigated 44 children; of them 9 term newborns and infants aged <2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies specifically investigated the safety of gadobutrol in the age group of toddlers, children, and adolescents aged 2 to 18 years. 23 , 24 Hahn et al recruited 138 patients undergoing routine MRI of the brain, spine, liver, kidneys, or MRA and assessed pharmacokinetics (PK) and safety of a single standard dose (0.1 mmol/kg body weight). They did not record any noteworthy changes in vital signs, cardiac rhythm, or oxygen saturation, neither any clinically significant change in renal laboratory parameters, serum creatinine, eGFR, total protein, albumin, blood urea nitrogen, or urine dipstick test.…”
Section: Safetymentioning
confidence: 99%